MENINGKATKAN PRESTASI BELAJAR MELALUI PENGGUNAAN TEKNIK JIGSAW - Mamahit, Meyke Machrita (Tumou Tou, 2020)
This study aims (1) to improve student achievement in class A semester VI Christian Religious Education Study Program Manado State Christian Religion Institute through cooperative learning with jigsaw techniques, (2) to increase interest and motivation to learn students in class A semester VI Education Study Program Christian Religion Institute of Manado State Christian Religion through cooperative learning with jigsaw techniques. This research is classroom action research. Total population of 145 people and a sample of 14 people. The research data were obtained from test scores on pre-cycle, cycle 1, cycle 2 and questionnaire. The results showed that cooperative learning with jigsaw techniques can significantly improve achievement, interest and motivation of students in class A semester VI of the IAKN Manado Christian Religious Education Study Program. The percentage of the number of students who obtained a minimum passing grade achievement increased from 60% in the pre-cycle to 80% in cycle 1, and to 90% in cycle II. Students' interest and learning motivation increases, from 70% in cycle 1 to 90% in cycle 2.